NaFeTiO4/Fe2O3–FeTiO3 as heterogeneous catalyst towards a cleaner and sustainable biodiesel production from Jatropha curcas L. oil. (1st July 2021) - Gutiérrez-López, Adriana N.; Mena-Cervantes, Violeta Y.; García-Solares, Selene M.; Vazquez-Arenas, Jorge; Hernández-Altamirano, Raúl
Abstract: A low-cost NaFeTiO4 /Fe2 O3 –FeTiO3 catalyst is synthesized using a solid-state method for biodiesel production using Jatropha curcas L. oil (JCO). X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) confirm the successful synthesis of this material. A Box-Behnken design (BBD) was used to perform a multivariate statistical optimization screening the following factors: methanol: oil molar ratio (6:1 to 16:1), catalyst load (0.15–15 wt%), and stirring rate (125–700 RPM); while maintaining the reaction time and temperature at 1 h and 65 °C, respectively. The triglyceride conversion into methyl esters is measured using Fourier Transform Infrared Spectroscopy (FT-IR) and used as a response variable. The maximum conversion of 93.24% is obtained using the following optimized reaction conditions: 12.47:1 MeOH: oil molar ratio, 13.80 wt% catalyst, and 590 RPM. It is found from the statistical analysis that catalyst load is the most relevant factor affecting the transesterification reaction, which otherwise, the biodiesel production does not occur when used at the lowest limit (0.15 wt%). The fatty acid methyl ester (FAME) composition obtained from Jatropha curcas L. oil is determined using Proton Nuclear Magnetic Resonance 1 H-NMR and Gas Chromatography (GC). Graphical abstract: Image 1 Highlights: Synthesis of NaFeTiO4 /Fe2 O3 –FeTiO3 via a facile and low-cost solid-state method. Reaction parameters screened out using Box-Behnken design. Methyl esters conversion of 93.24% with a reaction time of 1 h. Catalyst load and stirring rate strongly affect the biodiesel production. FAME conversion drops from 93.24% to 47.54% at fifth cycle of catalyst reusability.